2001
DOI: 10.1509/jmkr.38.4.494.18901
|View full text |Cite
|
Sign up to set email alerts
|

Do We Really Know how Consumers Evaluate Brand Extensions? Empirical Generalizations Based on Secondary Analysis of Eight Studies

Abstract: The authors investigate the empirical generalizability of Aaker and Keller's model of how consumers evaluate brand extensions. Various replications have reported different results. Using a comprehensive data set containing the data from the original study and seven replications conducted around the world, the authors undertake a secondary analysis to understand what generalizations emerge. The study has implications for the understanding of how brand extensions are evaluated and how empirical generalizations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
280
3
23

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 321 publications
(324 citation statements)
references
References 23 publications
(42 reference statements)
18
280
3
23
Order By: Relevance
“…All three studies find consistent effects using a method of systematically varying relative manufacturing difficulty. A review of eight brand extension studies found inconsistent effects for manufacturing difficulty on attitudes toward an extension (Bottomley and Holden 2001). Those studies examined the difficulty of the extension but not of the parent.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All three studies find consistent effects using a method of systematically varying relative manufacturing difficulty. A review of eight brand extension studies found inconsistent effects for manufacturing difficulty on attitudes toward an extension (Bottomley and Holden 2001). Those studies examined the difficulty of the extension but not of the parent.…”
Section: Resultsmentioning
confidence: 99%
“…Although brand extension research has indicated that an extension's perceived difficulty may influence attitudes toward that extension (Aaker and Keller 1990), the evidence is mixed. The perceived difficulty of manufacturing the extension is associated with positive evaluations in some studies and with negative evaluations in other studies, and sometimes it has no significant relationship with extension evaluations (Bottomley and Holden 2001).…”
Section: Effects Of the Difficulty Of Manufacturing A Productmentioning
confidence: 95%
See 1 more Smart Citation
“…This reaction might be related to the perception of difficulty of manufacture (Johnson and Folkes, 2007), which shares a positive relationship with a consumer's overall evaluation of a brand (Bottomley and Holden, 2001). Therefore, although the technology behind some innovations may not be clearly visible to consumers it appears as if consumers may form a judgment about how technologically innovative a product is and this perception may influence their evaluations of a product's innovativeness.…”
Section: Key Findings and Insights From The Qualitative Researchmentioning
confidence: 99%
“…These studies have generated important insights into a number of areas of the process of consumers' attitudes towards and evaluations of brand extensions, e.g., brand and category-level fit (Boush et al, 1987;Broniarczyk and Alba, 1994;Bhat and Reddy, 2001;Park et al, 1991;Lau and Phau, 2007;Milberg et al, 2013), the effect of prior knowledge of the extension category or the brand (Boush and Loken, 1991;Bottomley and Holden, 2001), forward and reciprocal spillover effects between parent and extension (Jacobson and Lane, 1997;Balachander and Ghose, 2003), consumer motivation and expertise (Broniarczyk and Alba, 1994), advertising and marketing strategy (Balanchander and Ghose, 2003;Dens and De Pelsmacker, 2010) and purchase intention (Lane, 2000;Bhat and Reddy, 2001). As pointed out by Czellar (2003), the vast majority of existing research focuses thus on consumer characteristics, predominantly rooted in cognitive psychology (e.g., Aaker and Keller, 1990;Park et al, 1991;Broniarczyk and Alba, 1994;Bhat and Reddy, 2001;Monga and John, 2010), and pays little attention to other factors such as consumer heterogeneity, competitor and distributor activity.…”
Section: Research Gap: the Relevance Of The Studymentioning
confidence: 99%